Morphology of the parotid gland of rats under conditions of experimental intrauterine growth retardation. - Reshetnikova, O. S.; Morozov, S. A. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Child’s dental caries is one of the most topical problems in practical dentistry. In case of neglecting of prevention and treatment it can lead not only to local complications, but also to systemic processes. Many studies have shown the dependence of tooth tissue destruction on changing the properties of oral fluid. Therefore the problem of salivary glands pathomorphology and function are regarded as promising directions for further fundamental research. Objective. According to this, the aim of the study was an experimental investigation of the effect of intrauterine growth retardation on the structural remodeling of the parotid salivary gland. Methods. Parotid glands of 65 newborn rats, including 35 animals with signs of IUGR and 30 controls born after physiological pregnancy were the material of the study. Tissue samples of parotid glands were studied microscopically. The differences were analyzed by methods of mathematical statistics; data were compared with controls by Student’s t-test. Results revealed the reduction of the number and size of the parotid gland’s lobules with a concomitant stromal connective tissue proliferation. The vessels were hyperemic. There were also perivascular foci of stromal edema. Glandular acini had some features of the degenerative changes of epitheliocytes – sign of hydropic dystrophy. Morphometric study of the structural organization of the parotid glands of the newborn rat in case of IUGR defined the reduction in parenchymal VF to 25,00 ± 6,96% and increases VF of the stroma to 35,67 ± 4,29% (in controls - 51,72 ± 7,04 and 23,70 ± 3,25%, P <0.05, respectively). Conclusion. Results of the research are considered in terms of structural basis of functional deficiency of the parotid gland and the possible impact of developmental retardation on oral fluid properties.